2018
DOI: 10.1002/jlb.3a0717-294rr
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14, CD163, and CD27 biomarkers distinguish ART-suppressed youth living with HIV from healthy controls

Abstract: Soluble inflammatory and lymphocyte biomarkers sufficiently distinguish YLWH from HC. Persistent macrophage activation biomarkers may provide a means to monitor consequences of HIV infection in fully suppressed YLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Contradictory results have been reported from different studies on the effect of cART on sCD14 (3335) due to a variety of contributors (36, 37). On the other hand, sCD163, a marker of vascular inflammation (38) and neurocognitive impairment (39), was higher in PLHIV than in healthy controls, which is in contrast to previous reports (40) but in line with other studies which showed that sCD163 was higher compared to the HIV-negative controls within 2 years of therapy (41, 42). The novelty of our study was to explore a large panel of inflammatory markers and we showed significantly higher levels of MMP1 (43), ADA (44), CD8A (16), SLAMF1 (45), and CCL23 (46) in PLHIV on long term ART.…”
Section: Discussionsupporting
confidence: 67%
“…Contradictory results have been reported from different studies on the effect of cART on sCD14 (3335) due to a variety of contributors (36, 37). On the other hand, sCD163, a marker of vascular inflammation (38) and neurocognitive impairment (39), was higher in PLHIV than in healthy controls, which is in contrast to previous reports (40) but in line with other studies which showed that sCD163 was higher compared to the HIV-negative controls within 2 years of therapy (41, 42). The novelty of our study was to explore a large panel of inflammatory markers and we showed significantly higher levels of MMP1 (43), ADA (44), CD8A (16), SLAMF1 (45), and CCL23 (46) in PLHIV on long term ART.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings are consistent with those of previous studies that, in mainly chronically-infected patients, compared treated PLHIV to appropriate controls [ 11 , 18 , 21 ]. Interestingly, a recent study from the MACS cohort reported abnormally elevated concentrations of certain inflammatory biomarkers including sCD14, sTNFRII, but also CXCL10 and TNF-α, even in MSM who reported 100% ART adherence [22] .…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a recent study from the MACS cohort reported abnormally elevated concentrations of certain inflammatory biomarkers including sCD14, sTNFRII, but also CXCL10 and TNF-α, even in MSM who reported 100% ART adherence [22] . sCD14 and sCD163 have been identified several times as the markers that best discriminated between HIV-infected and uninfected individuals [ 11 , 18 , 21 ]. In an older population, with a median age 59 years, Booiman et al did not observe any difference in sCD14 according to HIV status, but still reported elevated levels of sCD163 and I-FABP in PLHIV after a median of eight years of ART [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, plasma levels of IP-10, sCD14, and sCD163 were measured. These molecules have been proposed as markers of persistent inflammation in HIV infection since their levels remain elevated despite years of cART, compared to healthy donors [30][31][32][33][34][35][36][37]. Both IP-10, sCD14, and sCD163 were detected in all the samples tested.…”
Section: Cohort Description and Experimental Determinationsmentioning
confidence: 96%